Education Supervision Visit on Implemented Inspection of Office Spatial Management at State Elementary School - Ahmad Supono (Universitas Muhammadiyah Enrekang, 2023)
An office layout that is not good will waste energy, time, create a feeling of discomfort and discomfort so that the enthusiasm and enthusiasm for teaching decreases. In order to avoid this, the arrangement of office layouts must be good and able to create a comfortable and pleasant teaching atmosphere. It is hoped that this will encourage teachers in teaching to be more enthusiastic in completing their teaching assignments. The research procedure used was to use the school action research model developed by Kemmis & Taggart (2000), where in principle there are four stages of activity, namely planning, action, observation and evaluation. ) and reflecting. Based on the results of the analysis and discussion of cycle I and cycle II mentioned above, it can be concluded that: There is an increase in the teacher's ability to present ideas for improving office layout and utilizing landscaping in the environment around the school as teacher motivation in organizing teaching and learning activities at SD Negeri 01 Pancakarya, Ajung District, Jember Regency.